Cross-sectional Study to Explore the Knowledge about Oral Hygiene Aids among Dental Interns in India - Saquib, Shahabe Abullais; Alqahatani, Nabeeh Abdullah; N, Priyanka; Lokhande, Nitin (Journal of Dentistry Indonesia, 2018)
Plaque control is a cornerstone for periodontal maintenance, which can be accomplished via mechanical and chemical methods. Various oral hygiene aids are available to maintain the oral health status. Objective: To assess the knowledge of dental interns about the use of different oral hygiene aids in specific situations. Methods: This cross-sectional, one point-time, multicenter questionnaire-based survey was conducted to collect data from 393 participants (16 men; mean age: 24.6 + 5 years) who were randomly sampled from among dental interns across dental colleges in India. The questionnaires comprised 12 items. Results: Our data analysis revealed that dental interns possess adequate knowledge about the basic dental tools used for maintaining oral hygiene (60.1–79.7%). However, they possess less knowledge about the interdental aids pertaining to specific situations (35.8%) and the dose and frequency of use of chlorhexidine and other oral irrigation devices (32.9%). Conclusion: Although dental interns in India have basic knowledge about oral hygiene tools, there is a need for instilling greater awareness and learning about the use of oral hygiene aids in dental schools to upgrade the knowledge of students.